Logistics and exports. - Behar, A; Manners, P (CSAE (University of Oxford), 2008)
Drawing on a new and comprehensive measure of logistics quality, our gravity model suggests logistics in the exporting and partner-country can have an important impact on bilateral exports. A one standard deviation improvement in the exporter’s logistics quality, which for example would improve Gabon to the level of Guinea, would raise exports by almost 60%. Landlocked countries’ exports depend on their neighbours’ logistics, but their own logistics quality is not as important as for other countries. We also find that logistics act to reduce the trade effects of distance, but without eliminating them.